Baselines for the preparation of electronic textbooks - Lokar, Matija (Organizacija (Kranj), 2011)
The NAUK group (Advanced Learning Blocks group; http://www.nauk.si) is engaged in the development of theoretical and practical concepts of ICT use in all levels of education. Recently, the proposed introduction of electronic textbooks (e-textbooks) has become a major topic nationwide in Slovenia. There are multiple dilemmas to be solved, e.g. what a modern e-textbook is, what it should include, in what way should it differ from conventional textbooks, what tools and technologies should be used for its creation, etc. This paper attempts to make recommendations, which we believe should be followed by all the authors of e-textbooks.
Keywords: elektronsko izobraževanje; elektronska učna gradiva; učbeniki